Public Health Observatories in England – the first three years (Italian Journal of Public Health, 2004)
Public health observatories (PHOs) were created in England in 2000. Since then they have been engaged ina variety of activities to support the health improvement agenda in England. This article describes theseactivities, the key responsibilities and outputs of PHOs. It also describes the links with other observatoriesin Europe.
Keywords: observatories; health monitoring; regions; public health